Numerical Simulation on Electrical-Thermal Properties of Gallium-Nitride-Based Light-Emitting Diodes Embedded in Board. (24th October 2012) - Long, Xing-ming; Liao, Rui-jin; Zhou, Jing
Abstract : The electrical-thermal characteristics of gallium-nitride- (GaN-) based light-emitting diodes (LED), packaged by chips embedded in board (EIB) technology, were investigated using a multiphysics and multiscale finite element code, COMSOL. Three-dimensional (3D) finite element model for packaging structure has been developed and optimized with forward-voltage-based junction temperatures of a 9-chip EIB sample. The sensitivity analysis of the simulation model has been conducted to estimate the current and temperature distribution changes in EIB LED as the blue LED chip (substrate, indium tin oxide (ITO)), packaging structure (bonding wire and chip numbers), and system condition (injection current) changed. This method proved the reliability of simulated results in advance and useful material parameters. Furthermore, the method suggests that the parameter match on Shockley's equation parameters, R s, n ideal, and I s, is a potential method to reduce the current crowding effect for the EIB LED. Junction temperature decreases by approximately 3 K to 10 K can be achieved by substrate thinning, ITO, and wire bonding. The nonlinear-decreasing characteristics of total thermal resistance that decrease with an increase in chip numbers are likely to improve the thermal performance of EIB LED modules.